Strategi Good Village Governance: Membangun Tata Kelola Desa yang Transparan Melalui Penguatan Check and Balances dalam Pemerintahan Desa - Baskoro, Aji (Bestuurskunde: Journal of Governmental Studies, 2025)
This study examined the transformative role of village governance in advancing rural welfare in Indonesia, particularly following the enactment of the Village Law. This pivotal legislation grants villages autonomy to independently manage their resources and budgets, targeting enhanced rural prosperity through substantial financial allocations. The Village Law aims to empower local communities and strengthen their socio-economic foundations by addressing the persistent gaps in rural development since Indonesia’s independence. The study adopted a normative-juridical method integrated with a qualitative approach to scrutinize the legal norms and frameworks governing village governance and the Village Fund. A historical approach was used to trace the evolution of village governance structures, while a conceptual framework was employed to explore key principles of governance, accountability, and transparency. This multidimensional analysis underscores the necessity of implementing robust checks and balances, such as the Village Consultative Body (BPD) and public information systems, as fundamental pillars for ensuring transparency, accountability, and effective governance. Furthermore, the study highlights critical strategies for strengthening village governance, including capacity-building programs for village officials and fostering active community participation, particularly among marginalized groups. These initiatives aim to prevent the misuse of power, enhance public oversight, and support inclusive rural development. By embedding these mechanisms, villages can achieve sustainable governance that drives economic growth, improves community welfare, and bridges historical inequalities in rural development. The findings contribute to the broader discourse on good governance by emphasizing the interplay between legal frameworks, institutional capacity, and participatory practices in achieving equitable and effective rural governance.